The Manager : - Thompson, David W. (MTR Corp, 2004)
There are three factors that determine the profits of an organization, but only one over which management has any direct influence: the behavior of the people in the organization. From this book, managers will learn to: Assess the assets and liabilities of people quickly and accurately. Understand the motivations of subordinates, peers, and superiors. Appreciate the pervasive role of fear in driving the behavior of others. Effectively respond to disruptive, ineffective behavior by others. Evaluate the obstacles preventing a person from achieving their full potential. Give constructive feedback that results in overcoming these obstacles. Build a competent, cooperative, results-oriented team.